Development of Science Literacy Assessment Based on Multi Representation of Rectilinear Motion Concept to Investigate Students' Science Literacy Competencies - Ellianawati Ellianawati; Eresa Putri Meilanie; Bambang Subali (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
There have been many assessment instruments developed to measure student science literacy. However, literacy measurement instruments that pay attention to various intelligences and are reflected in the context of multiple representations have not been developed much. On the other hand, it is important to give every student the opportunity to succeed at his intelligence level. This study aims to determine the feasibility of a multi-representation based scientific literacy assessment instrument for high school physics on rectilinear motion concept as well as to describe students' scientific literacy skills and the mastery pattern of the rectilinear motion concept measured by the instrument developed. This research is a Research & Development (R&D) research. The test subjects were 262 high school students who had studied rectilinear motion concept in public high schools with A-accreditation. Data analysis conducted were validity test of instruments by experts; empirical test to obtain validity, reliability, difficulty level, and item difference; student responses to test offerings; profile of scientific literacy skills; and the pattern of mastery of the rectilinear motion concept. From the measurement results, it is evident that the profile of the average scientific literacy ability of high school students is still in the unsatisfactory category. The pattern of mastery of the concept of straight motion based on the modes of representation ranging from the most difficult to the easier ones is graphical, pictorial, verbal, and mathematical representations. This data could indicate that learning by practicing literacy skills still can be improved.